Intellectual Property Office of thePhilippines the country's premier center for innovation, industry, science and research - Formalejo, Pacian Francis P. (Quezon City College of Architecture, University of the Philippines Diliman, 2014)
The backbone of this thesis seeks to provide a facility that will help promote economic, technological and sociocultural development in the country. The project will be the Intellectual Property Office of the Philippines which will be providing spaces for research and development, innovation and exposition of new products and inventions as outputs of the design process. It will be a venue for innovation which leads to economic growth according to Greenhalgh and Rogers (2010) through the effective use of the Intellectual Property System in all levels of society to create, protect the use and enforce intellectual property and as well as to promote creativity and culture. This study will focus primarily on the architectural design solution to address the issue on space allocations of the IP System that will help realize creativity and innovation among its users.
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Intellectual Propterty Office -- Designs and plans -- Philippines